The Open Library. Financial and Human Aspects - Mittler, Elmar (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
The year 2000 Seminar of the LIBER architecture group in Warsaw provided an opportunity to discuss new frontiers in the development of library buildings. New ways of financing are needed in an economically fast changing world. It was impressive to hear from Robert Rzesos about the successful financing activities for the University library of Warsaw. Alan MacDougall gave an outstanding paper concerning successful fundraising activities for new library buildings, based on experiences he has made in Dublin. Graham Bulpitt gave an overview on income generation through library buildings.